Clinical Profile and outcome of Dengue Fever in Under 5 Children Admitted at a Tertiary Care Hospital, Dhaka - Ahmed, Tasnima; Nahar, Jebun; Mohsin, Fauzia; Islam, Nasreen; Jashim, Sabrina (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Dengue has become a major public health problem in Bangladesh with gradually increasing infectivity and severity. Most vulnerable population are children especially children below 5 years of age. However, data regarding dengue among this age group is limited. The objectives of this study were to see the clinical and laboratory profile of dengue fever (DF) in children below 5 years of age and their outcome. Methods: This cross – sectional observational study was carried out in the department of Paediatrics, BIRDEM General Hospital from May 2023 to September 2023. One hundred eighty nine confirmed dengue cases were enrolled in the study. Their clinical profile and laboratory findings including haemoglobin (Hb%), haematocrit (Hct), total count of white blood cells (TC), platelet count (PC), serum alanine aminotransferase (S. ALT), serum aspartate aminotransaminase (S. AST), prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (aPTT), serum calcium and serum sodium level were documented and analyzed. Results: Among 189 children 57(30.1%) were infants and 132(69.8%) patients were aged 1 to 5 years. Depending upon the severity of dengue 98(51.8%) were classical dengue fever, 65(34.3%) and 14(7.4%) presented with dengue shock syndrome (DSS) and dengue heamorrhagic fever (DHF) respectively. Fever was present in all children, other common features were vomiting (34.9%), cough (25.9%), dehydration (26.9%), pleural effusion (34.3%), ascites (23.2%) and skin rash (18.5%). Shock were present in 41.1% cases. Warning signs like restlessness, lethargy, altered level of consciousness, convulsion was present in 16.4%, 9.5%, 2.6% and 11.6% respectively. All the children were improved and discharged. Conclusion: In this study dengue presented classically in most of the children. Dengue shock syndrome and dengue haemorrhagic fever were below 10%. The outcome was excellent with no modality. Early reporting to hospital appeared important. J Bangladesh Coll Phys Surg 2023; 41: 25-28